(untitled) (Al-Aasar, 2025)
The concept of athar occupies a pivotal position within Islamic scholarship, especially in the fields of Hadith, Uṣūl al-Fiqh, and Qur’anic exegesis. Linguistically, the term denotes traces, indications, or remnants left behind, while technically it refers to non-Prophetic narrations attributed to the Companions (Ṣaḥābah) and Successors (Tābiʿīn). When specifically linked to the Companions of the Prophet (peace be upon him), it is termed Āthār al-Ṣaḥābah, comprising their statements, actions, legal verdicts, and individual reasoning (ijtihād). These āthār are foundational for understanding how the first generation internalized, practiced, and transmitted the teachings of the Qur’an and Sunnah. This study examines the lexical and terminological nuances of athar through major Arabic lexicons and traces its usage in classical Islamic literature. It further explores the legal authority of the āthār, demonstrating that the majority of Sunni jurists—including Mālik, Aḥmad, the later view of al-Shāfiʿī, and most Ḥanafīs—consider the statements of the Companions as binding or highly persuasive, especially when uncontested or widely accepted among them. The paper also highlights the indispensable role played by the āthār in fiqh, tafsīr, and the formulation of legal maxims. Finally, it surveys the principal classical sources preserving these narrations, such as the Muṣannaf works of Ibn Abī Shaybah and ʿAbd al-Razzāq, early tafsīr collections, and biographical compilations, emphasizing that an authentic understanding of Islam is incomplete without the epistemic guidance of the Companions.